2003
DOI: 10.1097/00000478-200312000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Current Diagnostic Methods of HER-2/neu Detection in Breast Cancer With Special Regard to Real-Time PCR

Abstract: In this study we compare different diagnostic methods to measure HER-2/neu gene amplification in breast cancer with special regard to real-time polymerase chain reaction. Fifty specimens of breast cancer were analyzed, and the use of laser-assisted microdissection prior to PCR was investigated. A total of 38 of 50 cases showed HER-2/neu overexpression in immunohistochemistry. In the 2+ scored group, 2 of 23 cases turned out to be amplified after FISH analysis and 14 of 15 cases in the 3+ group were amplified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Previous studies have shown an equivalence of 80-90% among FISH and qPCR techniques on samples assessed as 3+ by IHC (9,10). In this sense, our results confirm the same percentage of accuracy, as we only had one discrepancy among the eight samples analyzed (ID 14).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies have shown an equivalence of 80-90% among FISH and qPCR techniques on samples assessed as 3+ by IHC (9,10). In this sense, our results confirm the same percentage of accuracy, as we only had one discrepancy among the eight samples analyzed (ID 14).…”
Section: Resultssupporting
confidence: 87%
“…20 In addition, a tissue microarray containing 93 cases of invasive female breast cancer with detailed followup data of 70 cases comprising 30 years was included in our study. All 144 cases were analyzed immunohistochemically using commercially available antibodies directed against AP-2alpha and AP2gamma.…”
Section: Resultsmentioning
confidence: 99%
“…The study collective has been intensively characterized previously with respect to tumor stage, tumor grade and HER2/neu status. 20 In addition, a tissue microarray containing 93 additional cases collected at the Department of Gynecology and Obstetrics, University of Heidelberg, Germany was analyzed. To account intratumoral heterogeneity two tissue samples per case have been mounted on the tissue microarray.…”
Section: Patientsmentioning
confidence: 99%
“…Good concordance, however, was reported between FISH and Qrt-PCR on the DNA as well as the RNA level (34,35).…”
Section: Correlation Between the Her2 Status Assessed Either By Qrt-pmentioning
confidence: 94%